Literature in Islam and its Role Strengthening Nationalism - Ainun Haq, Vick; Amirudin; Rodiallah Ma, Alkaf (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The modern era has a positive impact on nationalism and religious matters as well as on mafsadat, the literary study of a knife, that has a critical-casuistic impact on civilization. Both of them are related since religion frequently uses literature as a vehicle for teachings (Islam; Rahmatan lil-alamin) and literature frequently incorporates religious ideals into its themes. This essay seeks to discuss the deep review of literature in Islam from history to the most recent effects. This study's methodology uses a qualitative approach with a type study library, information drawn from books and journals, and a focus on literature, Islam, and nationalism as main sources and pertinent secondary sources, respectively. The study's next study showed how the Indonesian nation's diversity can be strengthened in the face of the negative effects from globalization. So, this study's discussion will be focused; (1) The existence of Islamic literature in Indonesia (2) Indonesian intellectuals' the use literature as a medium for da'wah based religious moderation.